Effect of Modified Yijinjing Exercise on Sleep Quality in Stroke Patients with Sleep Disorder during Convalescent Period - Li ZHANG; Jun HU; Xin XUE; Xueming JIN (康复学报)
Objective:To explore the clinical effect of modified Yijinjing exercise on stroke patients with sleep disorder during convalescent period, and provide evidence for clinical rehabilitation of stroke sleep disorder.Methods:A total of 50 stroke patients with sleep disorder during convalescent period were randomly divided into the experimental group and the control group, with 25 cases in each group. The control group was subjected to routine rehabilitation training. In addition to routine rehabilitation training, the experimental group also performed modified Yijinjing exercise,60 min each time,3 times a week for 4 weeks. Before and after the intervention, the Pittsburgh Sleep Index Scale (PSQI) was used to assess the patient's sleep quality, and the patient's quality of life was assessed by using the Short Form 36 Health Survey Questionnaire (SF-36).Results:After the intervention, the total scores of PSQI, sleep quality, sleep time, sleep efficiency and daytime function scores of the experimental group were lower than those before the intervention, the scores of the physical component summary and mental component summary were higher than those before the intervention, and the differences were statistically significant (P<0.05 or P<0.001). Compared with the control group, the before and after intervention score difference of PSQI total score, daytime function, physical component summary and mental component summary in the experimental group was statistically significant (P<0.05).Conclusion:Modified Yijinjing exercise can improve the quality of sleep and life in stroke patients with sleep disorder during convalescent period.